Effect of the Simultaneous Variation in Blade Root Chord Length and Blade Taper on Helicopter Flight Control Effort - Tugrul Oktay; Firat Sal (International Journal of Aerospace Engineering)
In this study, the effect of simultaneous variation in blade root chord length and blade taper on the control effort of helicopter flight control system (i.e., FCS) of a helicopter is investigated. Therefore, helicopter models (i.e., complex, control-oriented, and physics-based models) including the main physics and essential dynamics are used. The effect of simultaneous variation in the blade root chord length and blade taper (i.e., in both chordwise and lengthwise directions dependently) on the control effort of an FCS of a helicopter and also on the closed-loop responses is studied. Comparisons in terms of the control effort and peak values with and without variations in the blade root chord and blade taper changes are carried out. For helicopter FCS variance-constrained controllers, specific output variance-constrained controllers are beneficial.